The Role of Digitalization in Health Financing: Advancing Management Practices in Healthcare - Enji Azizi; Mira Nurhikmat; Yulaikah Yulaikah; Siti Nur Aliyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Background: Digitalization is fundamentally reshaping health financing, enabling more efficient management of healthcare resources, improving service delivery, and increasing accessibility. This systematic review explores the intersection of digital tools and financial health systems, examining their transformative potential.Objective: The primary aim of this review is to identify the impact of digitalization on healthcare financial management, highlighting its benefits and addressing the challenges that arise during its implementation.Methods: A systematic review of 10 studies was conducted, focusing on digital health financing and employing PRISMA guidelines to ensure rigorous selection and analysis. The data extraction process identified thematic relevance, methodological rigor, and contextual insights.Results: The findings reveal that digitalization enhances resource allocation, patient accessibility, and administrative efficiency. Technologies such as blockchain and artificial intelligence optimize transparency and predictive financial modeling. However, significant challenges include data security vulnerabilities and the integration of digital tools with legacy systems.Conclusion: Digital technologies present transformative potential for healthcare financing. However, strategic implementation, robust governance, and cross-sector collaboration are critical to overcoming challenges and maximizing the benefits of digitalization. By addressing these needs, digitalization can create sustainable, inclusive, and equitable healthcare systems for the future.